Dynamic regulation of P-glycoprotein in human brain capillaries - Avemary, Janine Verena; Salvamoser, Josephine D.; Peraud, Aurelia; Rémi, Jan; Noachtar, Soheyl; Fricker, Gert; Potschka, Heidrun (Molecular pharmaceutics, 2013)
Considering its role as a major blood-brain barrier gatekeeper, the dynamic regulation of the efflux transporter P-glycoprotein is of considerable functional relevance. In particular, disease-associated alterations in transport function might affect central nervous system drug efficacy. Thus, targeting regulatory signaling cascades might render a basis for novel therapeutic approaches. Using capillaries freshly prepared from patient tissue resected during epilepsy surgery, we demonstrate dynamic regulation of P-glycoprotein in human brain capillaries. Glutamate proved to up-regulate P-glycoprotein efflux transport in a significant manner via endothelial NMDA receptors. Both inhibition of cyclooxygenase-2 and antagonism at the glycine-binding site of the NMDA receptor prevented the glutamate-mediated induction of P-glycoprotein transport function in human capillaries. In conclusion, the data argue against species differences in the signaling factors increasing endothelial P-glycoprotein transport function in response to glutamate exposure. Targeting of cyclooxygenase-2 and of the NMDA receptor glycine-binding site was confirmed as an efficacious approach to control P-glycoprotein function. The findings might render a basis for translational development of add-on approaches to improve brain penetration and efficacy of drugs.